Exploring the potential role of EPSPS mutations for enhanced glyphosate resistance in Nicotiana tabacum - Bingjie Li; Bingjie Li; Chen Chen; Chen Chen; Mengmeng Cui; Yuhe Sun; Jing Lv; Changbo Dai (Frontiers in Plant Science)
Glyphosate is a widely used non-selective, broad-spectrum, systemic herbicide by interfering with the biosynthesis of aromatic amino acids. However, the emergence of glyphosate-resistant weeds has driven the need for enhanced herbicide resistance in crops. In this study, we engineered two mutant variants of the tobacco EPSPS gene through amino acid substitution (TIPS-NtEPSPS and P180S-NtEPSPS). These mutated EPSPS genes were overexpressed in tobacco under the control of CaMV35S promoters. Our results demonstrate that overexpression of TIPS-NtEPSPS significantly enhances glyphosate tolerance, allowing plants to withstand up to four times the recommended dose without compromising their fitness. This research highlights the potential of the TIPS-NtEPSPS mutant to improve herbicide resistance in tobacco, offering a viable approach for effective weed management.